PREVENTION AND MANAGEMENT FOR THE COMPLICATION OF THIRD MOLAR SURGERY : A SYSTEMATIC REVIEW - Wirastuti, Ida Ayu; Maharjana, Ida Bagus Nyoman; Soewondo, Prastuti (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Impacted third molar surgery is one of the most common procedures performed by maxillofacial surgeons and it is often attended by complications. Although clinical conditions associated with retained third molars are well understood, little is known about the impact of those conditions on the quality of life among affected patients. There is growing recognition that the impact of oral conditions on quality of life is an important outcome that can be quite useful in making treatment decisions. All the information in this review could be useful for the clinicians in order to show the surgical and pharmacologic parameters that may influence the postoperative discomfort in the third molar surgeries. Methods: This systematic review followed the recommendations in PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Some of the key words or Medical Subject Heading (MeSH) terms used in in the two data bases (Proquest and Google Scholar) were: (1) Third Molar Surgery, (2) Complication, (3) Prevention. The articles were published in English from 2009 to 2019. Results: Studies were eligible if they evaluated prevention and management for the complication of third molar surgery, and eight studies for qualitative synthesis. Of the eight articles, all studies were selected with Randomized Control Trial. Eight studies were included because they discussed the prevention and management of third molar surgery complication. Almost all of the practices of prevention and management of third molar surgery complication described that analgetic ibuprofen and paracetamol were used for decreasing the pain, and also amoxicillin tablet was used as an antibiotic for preventing high risk complication. According to studies, prophylactic use of chlorhexidine mouth rinse in third molar surgery are equally effective in keeping post operative infection to a minimum level in medically competent patient. Conclusions: All studies revealed that the most common complications of third molar surgery were pain, trismus, swelling, alveolar osteitis, and dry socket. Those studies discussed the prevention and management third molar surgery complication. Ibuprofen and paracetamol were used to decrease the pain, amoxicillin (1g) and amoxicillin/clavulanate (875/125mg) had similar efficacious in preventing infection after retained third molar extraction, but amoxicillin and clavunate (875/125mg) produced more gastrointestinal discomfort. Prophylactic use of chlorhexidine mouth rinse and gel in third molar surgery were equally effective in keeping post operative infection. Corticosteroid had a significant and sustained anti- inflammatory effects.